Effects of physical comorbidities on disability progression in multiple sclerosis. (30th January 2018) - Zhang, Tingting; Tremlett, Helen; Zhu, Feng; Kingwell, Elaine; Fisk, John D.; Bhan, Virender; Campbell, Trudy; Stadnyk, Karen; Carruthers, Robert; Wolfson, Christina; Warren, Sharon; Marrie, Ruth Ann
Abstract : Objective: To examine the association between physical comorbidities and disability progression in multiple sclerosis (MS). Methods: We conducted a retrospective cohort study using linked health administrative and clinical databases in 2 Canadian provinces. Participants included adults with incident MS between 1990 and 2010 who entered the cohort at their MS symptom onset date. Comorbidity status was identified with validated algorithms for health administrative data and was measured during the 1 year before study entry and throughout the study period. The outcome was the Expanded Disability Status Scale (EDSS) score as recorded at each clinic visit. We used generalized estimating equations to examine the association between physical comorbidities and EDSS scores over time, adjusting for sex, age, cohort entry year, use of disease-modifying drugs, disease course, and socioeconomic status. Meta-analyses were used to estimate overall effects across the 2 provinces. Results: We identified 3, 166 individuals with incident MS. Physical comorbidity was associated with disability; with each additional comorbidity, there was a mean increase in the EDSS score of 0.18 (95% confidence interval [CI] 0.09–0.28). Among specific comorbidities, the presence of ischemic heart disease (IHD) or epilepsy was associated with higher EDSS scores (IHD 0.31, 95% CI 0.01–0.61; epilepsy 0.68, 95% CI 0.11–1.26). Conclusions: Physical comorbidities are associated with an apparent increase in MS disability progression. Appropriate management of comorbidities needs to be determined to optimize outcomes.